Future Orientation and Work Readiness in the Context of Curricular Internship: An Industrial-Organizational Psychology Perspective - Cindy Vanesha; Suci Rahma Nio (IJIP : Indonesian Journal of Islamic Psychology, 2026)
This study aims to examine the relationship between future orientation and work readiness among psychology students who have participated in a curricular internship program using an industrial and organizational psychology perspective. This study employs a quantitative approach with a cross-sectional correlational design, involving 222 respondents selected using purposive sampling. Data collection was conducted using the Work Readiness Scale (WRS) and a future orientation scale with good reliability. Data analysis employed Spearman’s correlation. The results indicate a significant positive relationship between future orientation and work readiness (r = 0.680; p < 0.001), indicating a strong relationship. These findings underscore the importance of psychological factors in supporting students’ transition from the academic world to the workplace.This study contributes to the development of interdisciplinary psychology by integrating educational experiences and competencies in industrial and organizational psychology, and emphasizes the role of future orientation in enhancing.